Early Detection of Sepsisin High-Risk Obstetric Patients during Early Puerperium by Using MEOWS Chart - Tabassum, Tamanna; Chowdhury, Fahmida Islam; Dey, Laboni; Akter, Farzana; Sharmin, Dina; Hossain, Md Saidul; Chowdhury, Shahanara; Akter, Shahena (Journal of Chittagong Medical College Teachers’ Association, 2023)
Background: Globally, sepsis is the cause of over 260,000 maternal deaths a year. Every death is a tragedy, but 50% of these deaths can be prevented with appropriate medical care. For this reason, Modified Early Obstetric Warning System (MEOWS) chart is developed for the obstetric population to predict early signs of deterioration, monitoring of the patient and proper management of the patient. The aim of the study was to determine the efficacy of MEOWS for the early detection of sepsis in high-risk postnatal patients. Materials and methods: This prospective observational study was conducted in the Department of Obstetrics and Gynecology, CMCH from January 2021 to December 2021. According to inclusion and exclusion criteria 83 high-risk postnatal patients during early puerperium were selected purposively. Physiological parameters were checked hourly during the first four hours and every four hours there after until 24 hours postpartum and recorded on a MEOWS chart. Blood samples for investigation, such as total count, CRP and procalcitonin, were sent after 24 hours of observation. Serum procalcitonin level was compared with total MEOWS score. Results: Out of total 83 patients, majority 55(66.3%) of the patient's MEOWS score was 4 and 28(23.7%) of patients had score >4, which is suspicious for sepsis. Regarding procalcitonin level 53 (63.9%) patients had normal procalcitonin level (0.5ng/ml) and 30 (36.1%) patients had abnormal level of procalcitonin (>0.5 ng/ml) which is diagnostic for sepsis. MEOWS chart was 86.7% sensitive, 96.2% specific, 92.8% accurate with a positive and negative predictive value of 92.9% and 92.7% respectively for prediction of sepsis comparing the scoring systems with procalcitonin level. Conclusion: In low socioeconomic countries with limited resources for microbial culture and laboratory biomarkers of sepsis diagnosis, MEOWS score can be used as a bedside screening tool for early detection of sepsis and thus preventing sepsis related maternal morbidity and mortality. JCMCTA 2023 ; 34 (1) : 127-131